A polymer hybrid film based on poly(vinyl cinnamate) and poly(2-hydroxy ethyl methacrylate) for controlled flurbiprofen release - Alokour, Mamoon; Yilmaz, Elvan (Springer, 2021)
A crosslinked polymer hybrid film, ipn-poly(vinyl cinnamate-graft-2-hydroxy ethyl methacrylate)-v-poly(ethylene glycol dimethacrylate) was synthesized by UV initiation using poly(vinyl cinnamate) (polyVCi), 2-hydroxy ethyl methacrylate (HEMA) monomer and ethylene glycol dimethacrylate (EGDMA) crosslinker. Benzophenone (Ph2CO), was used as the photoinitiator. The synthesis was optimized by changing the concentration of HEMA, Ph2CO, EGDMA, and UV irradiation time. PolyVCi undergoes photocrosslinking by 2+2 photocylo addition while the monomer/crosslinker couple, HEMA/EGDMA, undergoes free radical polymerization and crosslinking to form EGDMA crosslinked polyHEMA. Hence, simultaneous interpenetrating polymer network (IPN) formation occurs. The IPN consists of dual network of photocrosslinked polyVCi and EGDMA crosslinked polyHEMA chains. Grafting of HEMA/EGDMA chains on the polyVCi backbone also occur during network formation. The chemical functionalities present in the polyVCi/polyHEMA/polyEGDMA IPN films obtained were characterized by FTIR and SEM analysis. The contact angle measurements show enhanced wettability of the IPN film compared to polyVCi surface. TGA analysis confirms thermal stability of the films. Swelling behavior of the films examined in water and in ethanol reveals the effects of the chemical natures of polyVCi and polyHEMA as well as that of crosslinking on the hydrophilicity of the film. The films were tested as drug release matrices using flurbiprofen. The drug was loaded into the film matrix during IPN formation under UV irradiation. PolyVCi/polyHEMA/polyEGDMA IPN proved to be a suitable release matrix for flurbiprofen demonstrating controlled release behavior and zero-order release kinetics. The release mechanism was confirmed by its Ritger-Peppas n value (1.00 to 1.42), which indicates super case II release.
Keywords: Photoinitiation; Poly(vinyl cinnamate); HEMA; IPN; Flurbiprofen; Controlled release